Shape‐Shifting Azo Dye Polymers: Towards Sunlight‐Driven Molecular Devices - Bushuyev, Oleksandr S.; Aizawa, Miho; Shishido, Atsushi; Barrett, Christopher J. (Macromolecular rapid communications., 2018)
The development of stimuli‐responsive polymers is among the key goals of modern materials science. The structure and properties of such switchable materials can be designed to be controlled via various stimuli, among which light is frequently the most powerful trigger. Light is a gentle energy source that can target materials remotely, and with extremely high spatial and temporal resolution easily and cheaply. Reversible light‐control over molecular mechanical properties in particular has in recent years attracted great interest due to potential applications as optical‐to‐mechanical conversion actuators and ‘devices’, enabling ‘molecular robotic machines’. In this review, some recent examples and emerging trends in this exciting field of research are highlighted, covering a wide variety of polymer hosts that contain azobenzene photo‐reversible switches. It is hoped that this review will help stimulate more interest towards the development of light‐reversible materials for energy harvesting and conversion, and their successful incorporation into a wide variety of current and future high‐tech applications in devices. Reversible light‐control over molecular mechanical properties has attracted great interest for the development of polymeric optical‐to‐mechanical actuators. In this review, recent examples and emerging trends in this exciting field of research are highlighted, covering a wide range of polymers containing azobenzene photo‐reversible switches, and their demonstration as functional “artificial muscles”, “devices”, and simple “molecular robotic machines”.